Biaxially oriented thin film containing cycloolefin polymer and alpha-olefin polymer, its preparation method and use in storage batteries

By using biaxially oriented films of cyclic olefin polymers and semi-crystal α-olefin polymers, the existing films have poor temperature stability and poor electrical performance under high temperature environments, and the low thermal shrinkage rate and good electrical performance of the films at high temperatures are achieved, which promotes the cost-effective and efficient production of the films.

JP7662594B2Active Publication Date: 2025-04-15BRUCKNER MASCHINEHAU GMBH & CO KG
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2022171901
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-29
Filing Date
2022-10-27
Publication Date
2025-04-15
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The existing films have poor temperature stability in high temperature environments, poor electrical performance, and are prone to cracks during production, resulting in insufficient film length and affecting economic production and use.

Method used

A biaxially oriented film consisting of 1-25% cyclic olefin polymer and 75-99% semi-crystalline α-olefin polymer, including at least one film with a glass transition temperature higher than the other cyclic olefin polymer, ensuring that the weighted average glass transition temperature is lower than the melting point of the semi-crystalline α-olefin polymer.

Benefits of technology

The high temperature stability and good electrical properties of the film are achieved, the low thermal shrinkage rate can be maintained at high temperatures, the working ability of the production equipment can be improved, and long-length films can be produced cost-effectively and efficiently.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662594000008
    Figure 0007662594000008
  • Figure 0007662594000009
    Figure 0007662594000009
  • Figure 0007662594000010
    Figure 0007662594000010
Patent Text Reader

Abstract

To provide a thin film containing a cycloolefin polymer having good electrical characteristics and low temperature shrinkage.SOLUTION: There is provided a biaxially oriented thin film containing a) 1 wt.% to 25 wt.% of at least two cycloolefin polymers having a glass transition temperature in the range from 120°C to 180°C and b) 75 to 99 wt.% of at least one semi-crystalline α-olefin polymer having a crystallite melting point in the range from 150°C to 170°C. The biaxially oriented thin film contains at least a first cycloolefin polymer and a second cycloolefin polymer, and the second cycloolefin polymer has a higher glass transition temperature than the first cycloolefin polymer. The weighted arithmetic mean of the glass transition temperatures of all cycloolefin polymers contained in the thin film is less than or equal to the weighted arithmetic mean of the crystallite melting point of all semi-crystalline α-olefin polymers contained in the thin film.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] beginning The present invention relates to a biaxially oriented thin film containing a) 1 to 25 wt % of at least two cycloolefin polymers having glass transition temperatures in the temperature range of 120°C to 180°C, and b) 75 to 99 wt % of at least one semi-crystalline α-olefin polymer having a crystalline melting point in the temperature range of 150°C to 170°C, wherein the biaxially oriented thin film contains at least a first cycloolefin polymer and a second cycloolefin polymer, the second cycloolefin polymer having a higher glass transition temperature than the first cycloolefin polymer, and the weighted arithmetic mean value of the glass transition temperatures of all the cycloolefin polymers in the biaxially oriented thin film is equal to or lower than the weighted arithmetic mean value of the crystalline melting points of all the semi-crystalline α-olefin polymers in the biaxially oriented thin film. [Background technology]

[0002] Thermoplastic resins in thin film form, used as insulators and dielectrics in the electrical industry, play a particularly important role. α-Polyolefins, especially polypropylene (PP), are the most widely used. Biaxially oriented polypropylene thin films used as dielectrics in storage batteries (condensers and capacitors) are described in the following Patent Documents 1, 2, and 3. Polyethylene thin films are generally excellent and suitable for use as dielectrics, but their large high-temperature shrinkage makes them unsuitable for use at high temperatures. Biaxially oriented polypropylene thin films are primarily used in thin-film storage batteries. This is due in particular to the transmission loss coefficient and withstand voltage characteristics of polypropylene. However, their temperature stability is limited (application range: 85°C to 105°C). At temperatures above 105°C, the voltage must be reduced to reduce the maximum allowable voltage. Use at temperatures above 115°C is severely restricted or impossible.

[0003] Compared to ordinary polyolefins, cycloolefin polymers (COC) have significantly better heat distortion resistance. Cycloolefin polymers for use as thin battery membranes are known. Due to their high glass transition temperature and brittleness, biaxial stretching of cycloolefin polymers is difficult or impossible. The use of cycloolefin polymers in batteries is disclosed in Patent Documents 4, 5 and 6. Thin cycloolefin polymer membranes can only be produced in equipment specially manufactured for this purpose, but because high stretch ratios cannot be achieved, they are unsuitable for producing membranes suitable for use in batteries.

[0004] By using a composite resin of polypropylene and cycloolefin polymer, the heat resistance of the cycloolefin polymer can be utilized in storage batteries. Composite resins of polypropylene and cycloolefin polymer are disclosed in Patent Documents 7, 8, and 9. Patent Documents 10 and 11 describe special thin films used in thin-film storage batteries.

[0005] Patent Document 10 describes a thin film containing 10% to 45% by weight of a cycloolefin polymer having a glass transition temperature of 120°C to 170°C and a semi-crystalline α-olefin polymer (usually polypropylene) having a crystalline melting point in the range of 150°C to 170°C, the cycloolefin polymer having a glass transition temperature below the crystalline melting point of the α-olefin polymer. The thin film produced has a moderate surface roughness and low thermal shrinkage. The properties of the cycloolefin polymer described in Patent Document 10 are more pronounced at higher cycloolefin polymer content ranges. That is, when a high cycloolefin polymer content is incorporated, the thin film exhibits good thermal properties (including low shrinkage), but becomes brittle and has poor processability. In particular, when producing ultrathin thin films, the maximum possible elongation ratio is reduced, making it difficult to produce thin films at high elongation ratios. When a high elongation ratio is selected with a high cycloolefin polymer content, the thin film becomes brittle, making it impossible to produce a thin film of the required length. Figure 3 illustrates this problem. Other conditions being equal, it is necessary to reduce the longitudinal stretching ratio, particularly when using a high content of cycloolefin polymer in a conventional conveying process to produce thin films. The dots in Figure 3 indicate the maximum longitudinal stretching ratio at which thin films can be continuously produced when using the cycloolefin polymer at the indicated content. Modern conveying equipment typically produces thin films up to 30,000 meters in length. If the thin film is prone to cracking, it will be impossible to produce a film of the desired length, limiting its economical production and use.

[0006] Similar problems occur when cycloolefin polymers with high glass transition temperatures are used as thin film raw materials. The use of cycloolefin polymers with high glass transition temperatures substantially increases the brittleness of the cycloolefin polymer / polypropylene blend, making stable thin film production impossible or impossible even with optimized process parameters. For example, increased cracking during stretching during thin film production leads to an overall loss of thin film transport stability, making stable production impossible. Furthermore, thin films with lengths of less than 30,000 m are not possible.

[0007] Patent Document 10 discloses a method for producing a thin film for a storage battery at a sufficient elongation ratio at temperatures of 120°C to 125°C, but various applications, particularly storage batteries for automobile manufacturing, require high-temperature strength and an extremely thin film. Automobiles are often manufactured using electronic circuits in high-temperature environments such as the engine compartment or near the battery installation location. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2015 / 091829A1 [Patent Document 2] U.S. Patent Application Publication No. 5,724,222A [Patent Document 3] European Patent Application Publication No. 2481767A2 [Patent Document 4] European Patent Application Publication No. 0992531A1 [Patent Document 5] WO 00 / 63013A2 [Patent Document 6] Canadian Patent No. 2115196C [Patent Document 7] JP 05-262989 A [Patent Document 8] German Patent Application Publication No. 102010034643A1 [Patent Document 9] German Patent No. 19536043 [Patent Document 10] International Publication No. 2018 / 197034A1 [Patent Document 11] German Patent Application Publication No. 102017118202A1 [Patent Document 12] German Patent Application Publication No. 10242730A1 [Patent Document 13] German Patent Application Publication No. 102011109385A1 [Patent Document 14] International Publication No. 2014 / 094803A1 [Patent Document 15] International Publication No. 2015 / 007367A1 Summary of the Invention [Problem to be solved by the invention]

[0009] The object of the present invention is to provide a thin film having good electrical properties and low high-temperature shrinkage. A thin film with high thermal stability is desirable. It is preferable that thin films with the desired properties can be produced using conventional biaxially oriented thin film production equipment. It is important that thin films can be processed into long lengths using high-speed thin film production equipment. It would be even more advantageous if thin films could be produced at high elongation rates. Attempts are also being made to produce ultrathin thin films. For example, the ultimate goal of the present invention is to economically and efficiently produce thin films for storage batteries. [Means for solving the problem]

[0010] The present invention is implemented as follows: a) at least two cycloolefin polymers; b) at least one semi-crystalline α-olefin polymer, The total content of all cycloolefin polymers in the thin film ranges from 1% to 25% by weight, and all cycloolefin polymers in the thin film have a glass transition temperature range of 120°C to 180°C. The thin film comprises at least a first cycloolefin polymer and a second cycloolefin polymer, the second cycloolefin polymer having a higher glass transition temperature than the first cycloolefin polymer. The total content of all semi-crystalline α-olefin polymers contained in the thin film ranges from 75% to 99% by weight, and all semi-crystalline α-olefin polymers contained in the thin film have a crystalline melting point in the temperature range of 150°C to 170°C. The weighted arithmetic mean of the glass transition temperatures of all cycloolefin polymers contained in the thin film is equal to or less than the weighted arithmetic mean of the crystalline melting points of all semi-crystalline α-olefin polymers contained in the thin film, and all amounts reported are based on the total weight of the thin film. Unless otherwise specified, all weight percent contents reported herein are based on the total weight of the thin film.

[0011] The terms "orienting," "stretching," and "extending" used herein have the same meaning. The same applies to the corresponding terms "stretching," "extension," and "stretching."

[0012] The thin film of the present invention has a surprising combination of properties including good processability during manufacturing, high temperature resistance, and good electrical properties, which are not available with conventional thin films. Conventionally, the addition of a cycloolefin polymer with a high glass transition temperature has reduced processability, but in the present invention, it is surprising that the processability does not decrease even when a mixture of cycloolefin polymers having different glass transition temperatures is used.

[0013] The fact that the thin film of the present invention can be produced at an area draw ratio of about 50 demonstrates its good processability. The surface draw ratio is the product of the longitudinal draw ratio and the transverse draw ratio. A high surface draw ratio makes it possible to produce ultrathin thin films, for example, less than 5 μm. Ultrathin thin films are necessary to realize large-capacity storage batteries in a small volume (installation space). At the same time, multiple thin films can be produced at a film speed of 280 m / min after drawing or during winding (the usual film speed during thin film production is 250 m / min), making the thin film of the present invention economical to produce.

[0014] At the same time, the thin film of the present invention can be used as a dielectric in a storage battery at temperatures below 135°C, which is superior to conventional thin films. The thin film of the present invention exhibits temperature-electrical properties that are clearly superior to conventional thin films. Particularly in the automotive field, thin film storage batteries must meet high market demands in terms of temperature and voltage. The required operating temperature is 125°C or higher, particularly 135°C or higher. The present invention provides a biaxially oriented thin film that meets these requirements. Thus, the present invention develops a thin film containing an α-polyolefin and a cycloolefin polymer, opening up a wide range of new applications. The resulting thin film exhibits low transverse direction (TD) shrinkage, especially at high temperatures. Therefore, compared to the thin film of Patent Document 10, a cost-effective manufacturing method for producing ultrathin thin films at high temperatures can now be adopted. Furthermore, the thin film of the present invention has good electrical properties and a suitable surface roughness.

[0015] By combining two types of cycloolefin polymers, the total amount of the cycloolefin polymers can be reduced, and other effects of the present invention can be realized, such as improving the processing performance of the conveying device while maintaining good temperature resistance. Other effects have a favorable effect on the achievable elongation ratio, especially in the sequential drawing. Furthermore, the use of a small amount of cycloolefin polymer can reduce the manufacturing cost. There is no adverse effect on the electrical properties.

[0016] The high polypropylene content of the thin film of the present invention allows the thin film to be easily processed during production, and in particular allows for easy stretching. The use of two cycloolefin polymers with different glass transition temperatures provides surprisingly favorable high-temperature properties without compromising processability.

[0017] The semi-crystalline α-olefin polymer employed in the practice of the present invention is preferably a C3-C8 polyolefin polymer. The side chains may be linear or branched. This is usually polypropylene. Polypropylene imparts good processability and good electrical properties to the thin films of the present invention. This is usually a homopolymer of propylene in particular. However, the polypropylene may contain up to 10% by weight, preferably up to 5% by weight, of one or more C4-C8 polyolefins as comonomers. C4-C8 polyolefins selected from the group consisting of 1-butene, 1-hexene, and 1-octene are preferred.

[0018] The semi-crystalline polyolefin may be linear or branched, and may be a random copolymer or a block copolymer. It may also be an isotactic polymer, a syndiotactic polymer, or an atactic polymer. Isotactic polypropylene is preferred. The crystallinity of polypropylene is typically in the range of 35% to 80%, with a preferred range being 60% to 80%. The crystallinity is measured by differential scanning calorimetry (DSC) at a heating rate of 10 K / min in accordance with International Organization for Standardization Standard 11357. A particularly preferred crystallinity range is isotactic propylene with a crystallinity of 60% to 80%. Typical density range is 0.895 g / cm. 3 ~0.920g / cm 3The density is measured according to the International Organization for Standardization standard 1183.

[0019] The crystalline melting point range is preferably 160°C to 165°C. Methods for changing the crystalline melting point using a copolymer are known to those skilled in the art. The crystalline melting point was measured by differential scanning calorimetry (DSC) at a heating rate of 10 K / min in accordance with International Organization for Standardization Standard 11357. The semi-crystalline α-olefin polymer used preferably has a melt flow rate (Tg) range of 1 to 4 g / 10 min when measured at a temperature of 230°C under a load of 2.16 kg. Unless otherwise specified, the total melt flow index (melt flow index) in this specification was measured in accordance with International Organization for Standardization Standard 1133.

[0020] It is particularly preferred to form thin films from pure materials to impart advantageous electrical properties to the thin films. For this purpose, it is preferable to select α-polyolefin polymers of high purity quality. Because the presence of trace metals in battery dielectrics can adversely affect the electrical properties of the battery, it is particularly preferred that the thin films of the present invention have a low metal content. The total content of iron, cobalt, nickel, titanium, molybdenum, vanadium, chromium, copper, and aluminum in the thin films of the present invention is preferably less than 0.25 ppm.

[0021] Particularly suitable polymer types are the two polymers "Borclean® HC300BF" and "Borclean® HC312BF" available from Borealis, and polyolefins and "Prime Polymer" from The Polyolefin Company (TPC) of Singapore.

[0022] The cycloolefin polymer employed in the present invention may be a homopolymer or copolymer produced by a ring-opening polymerization reaction or, in particular, a ring-retaining polymerization reaction. The polymer is produced by a ring-retaining copolymerization reaction of a cyclic olefin such as norbornene with an acyclic olefin such as an α-olefin or ethylene, with ethylene being preferred. Information on the cycloolefin polymer used in the present invention is disclosed, for example, in Patent Document 10 and its cited references. Alternatively, a cycloolefin polymer may be used in which hydrogen is added to the double bonds remaining after polymerization.

[0023] Cycloolefin polymers prepared by the ring-sustaining copolymerization reaction of at least one olefin of formula (1) with at least one α-olefin of formula (2) are preferred.

[0024] [ka] however, n is 0 or 1, m is 0 or a positive integer, preferably 0 or 1; R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are each independently selected from the group consisting of hydrogen, halogen, alkyl, cycloalkyl, aryl, and alkoxy groups; R 17 , R 18 , R 19 and R 20 are each independently selected from the group consisting of hydrogen and alkyl groups; R 17 and R 19 can together form a saturated or unsaturated ring or ring system.

[0025] [ka] However, R 21 and R 22 are independent of each other and are selected from the group consisting of hydrogen and alkyl groups.

[0026] n is 0, m is 0 or 1, R 21 is hydrogen and R 22 is preferably a cycloolefin polymer selected from the group consisting of hydrogen and C1 to C8 alkyl groups. 1 , R 2 , R 5 ~R 8 and R 15 ~R 20 Among these, a copolymer of norbornene and ethylene and a copolymer of tetracyclododecene and ethylene are particularly preferred.

[0027] In the thin film of the present invention, the total cycloolefin polymer contained is most preferably a copolymer containing norbornene and ethylene as monomers. The polymerization reaction is preferably carried out in the presence of a metallocene catalyst.

[0028] The monomers employed in the production of the thin film cycloolefin polymer of the present invention are in a molar ratio of 95:5 to 5:95, and are preferably those of Chemical Formula 1 and Chemical Formula 2. The monomers may contain up to 10 mol % of one or more comonomers selected from the group consisting of propylene, pentene, hexene, cyclohexene, and styrene, based on the total amount of monomers.

[0029] Suitable cycloolefin polymers are known from U.S. Pat. No. 5,699,499. Topas® 6013, Topas® 6015, Topas® 6017, and Topas® 5013 from Topas Advanced Polymers GmbH (Frankfurt am Main, Germany), polymers designated "APEL COC" from Mitsui Chemicals, Inc., and polymers designated "ARTON COC" from JSR Corporation are particularly suitable. Topas® 6013 M07 / S04, Topas® 6015 S04, and Topas® 6017 S04 are most preferred. Polymers prepared by ring-opening polymerization of cyclopentadiene or norbornene are also suitable.

[0030] The glass transition temperature range of the cycloolefin polymer is 120° C. to 170° C., particularly preferably 130° C. to 170° C., with the optimum temperature range being 140° C. to 160° C. The glass transition temperature is measured by differential scanning calorimetry at a heating rate of 10 K / min in accordance with International Organization for Standardization standard 11357.

[0031] The cycloolefin polymer preferably has a molten resin fluidity index in the range of 0.3 to 4 g / 10 min, measured at a temperature of 230° C. under a load of 2.16 kg.

[0032] A small surface roughness is essential for the thin film of the present invention used in a storage battery, but if the surface roughness is too low, it will be difficult to process into a thin film placed on a conveying device. It is advantageous to adjust the molten resin fluidity indexes of the polymers used to impart an appropriate surface roughness that is not too high. The ratio of the molten resin fluidity index of the cycloolefin polymer to the molten resin fluidity index of the semi-crystalline α-olefin polymer is preferably in the range of 1:2 to 2:1.

[0033] The second cycloolefin polymer differs from the first cycloolefin polymer in that it has at least a higher glass transition temperature, which is preferably at least 3°C ​​higher, more preferably at least 5°C higher, and even more preferably at least 10°C higher than the glass transition temperature of the first cycloolefin polymer.

[0034] Although the thin film properties can be optimized by using multiple semi-crystalline α-olefin polymers, this is not essential to achieving the effects of the present invention. However, using multiple semi-crystalline α-olefin polymers makes the thin film manufacturing process somewhat more complicated. Therefore, it is preferable that the thin film of the present invention contains only one type of semi-crystalline α-olefin polymer, and that the weighted average of the glass transition temperatures of all the cycloolefin polymers contained in the thin film is equal to or lower than the crystalline melting point of the semi-crystalline α-olefin polymer. It is particularly preferable that the thin film of the present invention contains only one type of semi-crystalline α-olefin polymer, that is, polypropylene.

[0035] The thin film of the present invention must contain at least two types of cycloolefin polymers, and may contain two or more types of cycloolefin polymers, for example, three or four types of cycloolefin polymers. At least two of the cycloolefin polymers must have different glass transition temperatures. Furthermore, two or more types, for example, three or four types of cycloolefin polymers having different glass transition temperatures may be contained, but the thin film of the present invention usually contains only one type of semi-crystalline α-olefin polymer other than the first cycloolefin polymer and the second cycloolefin polymer, and does not contain multiple cycloolefin polymers.

[0036] The thin film of the present invention preferably contains only one semi-crystalline α-olefin polymer, which is polypropylene, and does not contain any other cycloolefin polymers other than the first cycloolefin polymer and the second cycloolefin polymer, and both the first cycloolefin polymer and the second cycloolefin polymer contain norbornene and ethylene as monomers. This type of thin film is particularly suitable for use in storage batteries.

[0037] The biaxial orientation of the thin films of the present invention is substantially affected by the cycloolefin polymer content and the glass transition temperature of the cycloolefin polymer. The thin films of the present invention are particularly suitable for use in storage batteries when the total cycloolefin polymer content of the thin film is in the range of 10% to 25% by weight and the total semi-crystalline α-olefin polymer content of the thin film is in the range of 75% to 90% by weight. Thin films in which the total cycloolefin polymer content of the thin film is in the range of 10% to 20% by weight and the total semi-crystalline α-olefin polymer content of the thin film is in the range of 80% to 90% by weight are particularly preferred. Thin films in which the total cycloolefin polymer content of the thin film is in the range of 15% to 20% by weight and the total semi-crystalline α-olefin polymer content of the thin film is in the range of 80% to 85% by weight are optimal. The first and second cycloolefin polymers each preferably have a content of at least 3% by weight, and more preferably at least 5% by weight.

[0038] The thin film of the present invention contains the first cycloolefin polymer and the second cycloolefin polymer in an amount of typically 3 to 22% by weight, preferably 3 to 17% by weight, and particularly preferably 5 to 15% by weight. When the cycloolefin polymers are used in the amounts described above, the multiple effects produced by using multiple cycloolefin polymers become particularly pronounced.

[0039] In addition to the polymer, the thin film can contain conventional auxiliary agents and additives. The auxiliary agents and additives are typically added in amounts of 5% by weight or less, preferably 2% by weight or less. The auxiliary agents and additives can be selected from the group consisting of fillers, pigments, dyes, oils, waxes, plasticizers, UV stabilizers, delustering agents, preservatives, biocides, antioxidants, antistatic agents, flame retardants, and reinforcing agents. However, thin films containing no other components other than the polymer are preferred. Thin films free of solid agents (other than the polymer), especially inter-film adhesion inhibitors (antiblocking agents) and fillers, are particularly preferred. Solid components can adversely affect electrical properties.

[0040] The preferred longitudinal heat shrinkage of the thin film of the present invention is a maximum of 5%, particularly preferably a maximum of 3%, and optimally a maximum of 2%. The preferred transverse (TD) heat shrinkage of the thin film of the present invention is a maximum of 0.5%, particularly preferably a maximum of 0.1%, and optimally a maximum of 0.05%. The transverse heat shrinkage, which can cause battery failure, is extremely important for battery applications. In particular, the thin film should simultaneously have heat shrinkage values ​​in both directions. Therefore, the thin film of the present invention is particularly preferably a longitudinal heat shrinkage of a maximum of 5% and a transverse heat shrinkage of a maximum of 0.5%. The optimal longitudinal heat shrinkage of the thin film of the present invention is a maximum of 2%, and the optimal transverse heat shrinkage is a maximum of 0.05%. In both cases, the heat shrinkage is measured at 130°C for 5 minutes according to DIN-ISO standard 11501, and the thin film of the present invention having a transverse heat shrinkage value at 140°C is optimal.

[0041] Although the roughness of a thin film, which is important for electrical properties, is preferably small, the thin film of the present invention, which typically does not contain an inter-film adhesion inhibitor, must be given at least some surface roughness to ensure the thin film's processability. An excessively smooth thin film would slip on the conveying rollers and be difficult to process in industrial factories. The surface roughness Ra of a thin film of the present invention is preferably in the range of 0.02 to 0.2 μm, preferably 0.04 to 0.12 μm. The ideal surface roughness Ra of the thin film of the present invention is in the range of 0.06 to 0.09. Surface roughness Ra is specified in German Industrial Standards (IE Standard) 4287. The thin film of the present invention shown in Figure 1 has a uniform fibrous surface structure on both sides. When measuring the surface roughness Ra of a thin film, the detector of the measuring instrument is guided along a specific length of the thin film surface to measure the surface irregularities. Because the surface protrusions of the thin film of the present invention are anisotropic, the surface roughness measured in the longitudinal (conveying) direction of the thin film may differ from that measured in the transverse direction. Preferably, both measurements are within the ranges stated above.

[0042] It is well known to those skilled in the art to appropriately select the temperature of the chill roll and the stretching preheating temperature to set the surface roughness of the thin film. When simultaneous stretching is performed, the temperature of the chill roll and the preheating temperature of the simultaneous stretching oven (e.g., simultaneous biaxial stretching apparatus) are adjusted relative to each other. When sequential stretching is performed, the temperature of the chill roll, the preheating temperature of the longitudinal stretching apparatus (MDO), and the stretching roller temperatures are adjusted relative to each other.

[0043] The thin films of the present invention have a preferred thickness in the range of 2 μm to 10 μm. A particularly preferred thickness of the thin films of the present invention is in the range of 2 μm to 5 μm. The film thickness is measured according to German Industrial Standard (DIN) specification 53370. Thin films in this thickness range are optimal for dielectric applications.

[0044] The width of the membrane of the present invention is typically in the range of 0.1 m to 10 m, and most often in the range of 5 m to 7 m.

[0045] The biaxially oriented thin film of the present invention preferably comprises: a) containing at least a first cycloolefin polymer and a second cycloolefin polymer, the first and second cycloolefin polymers containing, as monomers, 5 to 95% by weight of norbornene and 5 to 95% by weight of ethylene, respectively, based on the total weight of the cycloolefin polymer; and b) containing at least one semi-crystalline polypropylene; the total content of all cycloolefin polymers in the thin film is in the range of 10% to 25% by weight, all cycloolefin polymers contained in the thin film have glass transition temperatures in the range of 120°C to 180°C, the second cycloolefin polymer has a glass transition temperature at least 3°C ​​higher than that of the first cycloolefin polymer, the first cycloolefin polymer and the second cycloolefin polymer are each contained in the thin film at a content in the range of 5% to 15% by weight, the total content of all semicrystalline polypropylene in the thin film is in the range of 75% to 90% by weight, all semicrystalline α-olefin polymers in the thin film have crystalline melting points in the range of 150°C to 170°C, the weighted arithmetic mean of the glass transition temperatures of all semicrystalline polypropylenes contained in the thin film is equal to or lower than the weighted arithmetic mean of the crystalline melting points of all semicrystalline polypropylenes contained in the thin film, and the thin film has a thickness in the range of 2 μm to 10 μm, and unless otherwise specified, all amounts are values ​​relative to the total mass of the thin film.

[0046] The thin film of the present invention has one or more layers, and therefore constitutes a single-layer thin film or a multilayer thin film. At least one layer of the multilayer thin film has the above-mentioned composition of the thin film of the present invention. Furthermore, multiple layers of the multilayer thin film can be composed of the thin film of the present invention.

[0047] Thus, another embodiment of the present invention is a multilayer film comprising at least one layer of the inventive film described herein. A preferred embodiment of the multilayer film is a single layer of the inventive film, with an outer layer on one or both sides containing one or more semi-crystalline α-olefin polymers made of polypropylene. The multilayer film preferably has the same properties as a single layer, particularly with respect to shrinkage and surface roughness. The advantages of coextruded multilayer films with at least one outer polypropylene layer and at least one layer having the composition of the inventive film include the ability to tailor the surface properties, for example, by targeted crystallization control and spherulite formation, using techniques commonly known for polypropylene, battery, and membranes, and the presence of at least one layer of the inventive film can improve the mechanical and electrical properties of the multilayer film at high temperatures.

[0048] Particularly preferred are multilayer films having a single intermediate layer containing a semicrystalline α-olefin polymer and two outer layers (each formed from a film of the present invention). In this case, an intermediate layer containing only semicrystalline polypropylene as described herein is particularly preferred. This is because the dielectric properties are substantially affected by the 100% polypropylene intermediate layer, resulting in a film having an intermediate layer with very good dielectric properties and outer layers with improved temperature stability. Thin films without additional layers beyond the intermediate layer and outer layers are most preferred, although additional plating or metallization may be provided to the film, as described below.

[0049] Another embodiment of the thin film of the present invention is a coated thin film, in which at least one outer layer is coated with a material. In this specification, the term "coating" should be understood to mean a coating that is not produced during the extrusion of the thin film. The term "coating" means a coating that is applied to the finished thin film in a separate process after the thin film is produced. In a preferred embodiment, the thin film of the present invention is coated with a conductive layer on at least one side, and in an advanced embodiment of the present invention, a plated or metallized layer is formed on one or both sides of the thin film.

[0050] Since plating or metallization is required for use in thin film batteries, thin films having one surface coated with a plating or metal layer are most preferred. For this purpose, the surface of the thin film can be activated by corona treatment after stretching, and then the metal layer can be applied. Thin films having both outer surfaces metallized are also within the scope of the present invention.

[0051] Another embodiment of the present invention is a storage battery comprising the thin film described herein. The storage battery of the present invention has a breakdown voltage of 500 V / μm or more for a thin film thickness of 3.8 μm and 400 V / μm or more for a thin film thickness of 2.7 μm, measured at a temperature of 23°C using a direct current voltage according to the measurement method of German Industrial Standard (DIN EN 60243-2). Furthermore, when measured at a temperature of 25°C and in the frequency range of 1 kHz to 1 GHz, the breakdown voltage is 1 to 2 × 10 -4 Thin films and accumulators of the present invention are preferred which have the following dielectric loss factors: The loss factors are determined according to the German European Industrial Standard 60674-2 (VDE) standard. Accumulators with thin films having a dielectric constant in the range of 2 to 2.5 are preferred. The dielectric constant is also determined according to the German European Industrial Standard 60674-2 (VDE) standard.

[0052] Another embodiment of the present invention is a method for producing a thin film according to the present invention, comprising the steps of: producing, in particular by extrusion, a thin film comprising at least two cycloolefin polymers and at least one semi-crystalline α-olefin polymer; stretching the resulting thin film in the machine and cross directions to form a biaxially stretched thin film; Winding the resulting biaxially stretched film.

[0053] The above features and advantages of the thin film are equally applicable to the method and vice versa.

[0054] An areal stretch ratio of at least 40 is preferred for biaxially stretched films, especially wound films.

[0055] The film may be stretched in both the machine and transverse directions simultaneously, or may be stretched first in the machine direction and then in the transverse direction.

[0056] After drawing and before rolling, one or more of the following steps can be carried out to improve the film properties: Biaxially stretched thin film heat treatment process, Relaxation process of axially stretched films to purposefully reduce the two-area stretch ratio.

[0057] For example, the areal stretch ratio is at least 40 even after relaxation.

[0058] The method of the present invention is described in more detail below.

[0059] (1) Composition and dosage

[0060] The raw material for producing the thin film of the present invention may be a compound containing a semi-crystalline α-olefin polymer and a cycloolefin polymer. Semi-crystalline α-olefin polymer and cycloolefin polymer that match the composition are mixed and kneaded together immediately before being fed into an extruder, and then applied in batches. Granular or powdered resin is used as the raw material.

[0061] A unique material is prepared for each layer of the multi-layered thin film, with each layer material being prepared separately depending on the desired thickness of each layer.

[0062] The α-olefin polymer and cycloolefin polymer used in carrying out the thin film production method of the present invention correspond to the above-described structure of the thin film of the present invention.

[0063] (2) Extrusion process

[0064] One or more raw materials are fed into an extruder, where they are mixed, kneaded, and melted. When producing a thin film with only one layer, only one extruder is required.

[0065] When producing a thin film having multiple layers, each layer typically uses its own extruder. However, when producing multiple layers of the same composition, the multiple layers may be produced from the same resin granules. Then, the materials for two or more layers of the multiple layers are extruded from the same extruder. All multiple layers having the same composition can be extruded from a single extruder. Any type of extruder can be used.

[0066] Preferably, the extruder or extruders are selected from the group consisting of single screw extruders, cascade extruders and twin screw extruders.

[0067] Other mixers and refiners can be used, such as, for example, a Buss kneader or a planetary gear roll extruder. Preferred are extruders which operate in the preferred temperature range of 230°C to 280°C, particularly preferably in the temperature range of 240°C to 270°C.

[0068] (3) Nozzle and cooling roll

[0069] The melt exiting the wide-opening mold is deposited onto a chill roll.Multilayer film nozzles are preferably used to produce thin films having multiple layers.

[0070] It is preferable to properly position the thin film on the chill roll using a pinning device that brings the thin film into contact with the chill roll and applies a pressing force to the thin film to improve its placement. A suitable pinning device is an air knife that generates a directional air flow that applies a pressing force to the thin film in the direction of the chill roll.

[0071] The pinning device provides uniform contact of the film against the chill roll, helping to produce a smooth, flat cast film.

[0072] The preferred temperature range for the chill roll is 80°C to 100°C, more preferably 85°C to 95°C, with the optimum range being 90°C to 95°C. When producing an ultrathin film, the higher temperature in this temperature range is selected to set the desired roughness. For a film with a thickness of 3.8 μm produced in this embodiment, the appropriate temperature range is 90°C to 95°C, with the optimum temperature being 93°C.

[0073] (4) Stretching process

[0074] The heated cast film is then stretched in the machine direction (MD) and the transverse direction (TD).

[0075] In the thin film production method of the present invention, the longitudinal stretching ratio ranges, for example, from 3.0 to 7.0, or preferably from 5.0 to 7.0.

[0076] The range of the transverse stretch ratio in the thin film production method of the present invention is 7.0 to 13.0, preferably 8.0 to 11.0.

[0077] Sequential stretching, in which biaxial orientation or stretching in the machine direction and the transverse direction is carried out successively at different times, or simultaneous stretching, in which a thin film is stretched simultaneously in the machine direction and the transverse direction, is carried out.

[0078] (4.1) Sequential stretching process

[0079] The sequential stretching of the thin film is preferably carried out in the following manner.

[0080] a) Longitudinal stretching process

[0081] For example, a heated cast film is first stretched in the longitudinal direction. For this purpose, the cast film is fed to a longitudinal stretching apparatus (also called MDO), where it is sufficiently heated and then stretched in the machine direction. The film is stretched, for example, between a pair of rolls in the longitudinal stretching apparatus that rotate at different speeds.

[0082] This type of longitudinal stretching device is disclosed in, for example, Patent Document 13.

[0083] b) Lateral stretching process

[0084] It is preferable to carry out a transverse stretching step after the completion of the longitudinal stretching. At the time of transition to the transverse stretching step, the thin film stretched in the longitudinal direction is fed to a transverse stretching apparatus 10 (TDO).

[0085] A transverse stretching apparatus 10 shown in FIG. 1 generally includes a heating furnace 14 and two conveying rails 16 that serve as tracks for conveying the thin film.

[0086] The two conveying rails 16 are arranged mirror-symmetrically with respect to the axis of symmetry S of the drawing apparatus 10 and at least partially within the heating furnace 14. The conveying rails 16 extend outside the heating furnace 14 in an entrance area 18 where the thin film material 12 is fed into the drawing apparatus 10 and in an exit area 20 where the thin film material 12 is discharged from the drawing apparatus 10.

[0087] Excluding the entry and exit regions 18, 20, the transverse stretching apparatus 10 has at least three distinct regions 22, 24, and 26.

[0088] The mutually bordering regions 22, 24, 26 are arranged along the machine direction or normal withdrawal direction R of the transverse stretching device 10, with the introduction region 18 being followed in order by the first region 22, the second region 24, and the third region 26, and finally the exit region 20.

[0089] A pair of conveying rails 16 in a first region 22 (preheating region) of the transverse stretching apparatus 10 that borders the introduction region 18 are spaced apart from each other by a first distance.

[0090] In the second region 24 (stretching region), the distance between the two transport rails 16 increases, and finally reaches the second distance at the start of the third region 26 (heat treatment region).

[0091] On each of the pair of conveyor rails 16, a number of gripping devices 28 are guided along the conveyor rails 16 in a manner known per se. The gripping devices 28 are moved along the conveyor rails 16 by suitable drive means.

[0092] The transverse stretching device 10 is disclosed in, for example, Patent Document 14.

[0093] The thin film, which has already been stretched in the machine direction in the introduction region 18 and first region 22 of the stretching device 10, is transported in the drawing direction R and supplied to the second region 24 of the transverse stretching device 10, where it is stretched in the machine direction. For example, the machine direction side edges of the thin film are gripped by multiple gripping devices 28 on the conveying rails 16 provided on both sides in the drawing direction, and the thin film is stretched in the machine direction by pulling the thin film in the width direction via the gripping devices 28. The process of gripping the machine direction side edges of the thin film with the gripping devices 28 is also called "clipping." The multiple gripping devices 28 grip the machine direction side edges of the thin film, introduce it into the heating furnace 14 of the transverse stretching device 10, and move the thin film through the heating furnace 14.

[0094] The width E of the membrane 12 in the introduction area 18 corresponds approximately to the first distance between the transport rails 16 perpendicular to the withdrawal direction R.

[0095] The membrane 12 is then guided through a first region 22 while being heated.

[0096] In the next second region 24, the stretching region, where the distance between the two conveying rails 16 continuously increases, the thin film 12 is stretched laterally thinner and wider, and at the end of the second region 24, the thin film 12 has a second width.

[0097] After transverse stretching, the film 12 is relaxed by heating in a third region 26, after which the film 12 separates from the grippers 28 in the exit region 20 and leaves the transverse stretching apparatus 10 at a second width.

[0098] (4.2) Simultaneous stretching process

[0099] For example, simultaneous stretching is preferably performed by the pantograph method, spindle method, LISIM® linear motor biaxial thin film stretching method, or MESIM® simultaneous biaxial thin film stretching method, in which the thin film speed is 250 m / min or less.

[0100] The structure of the simultaneous stretching apparatus corresponds to that of the transverse stretching apparatus in terms of the basic arrangement of the various zones and the conveying rails in the heating furnace. The differences between the transverse stretching apparatus and the simultaneous stretching apparatus lie in the length of the zones and / or the temperature of the zones. For example, the gripping devices of the simultaneous stretching apparatus are individually accelerated along both conveying rails by linear motors, and the conveying devices stretch the thin film in the longitudinal direction. This type of simultaneous stretching apparatus is described, for example, in paragraphs

[0045] to

[0055] of Patent Document 15.

[0101] During simultaneous stretching, the unstretched cast film is fed into the inlet region of the simultaneous stretching device and gripped (clipped) by a plurality of gripping devices as described above.

[0102] The thin film is then applied to a first region 22 and heated.

[0103] The film is then fed to the second section 24 of the stretching zone where it is stretched simultaneously in the machine and transverse directions.

[0104] As in the case of the transverse stretching device, in the stretching region, the distance between the two transport rails is increased, thereby stretching the thin film in the transverse direction and increasing the width of the thin film.

[0105] Unlike the transverse stretcher, in the stretching zone 24, the multiple grippers 28 are accelerated to a speed (also referred to as the stretching speed) that is greater than the drive speed of the introduction zone, so that the film is also stretched in the machine direction.

[0106] In other words, the distance between the opposing grippers in the stretching zone increases in both the machine and cross directions, so that the film is stretched in both the machine and cross directions simultaneously. The machine and cross direction distances between the opposing grippers increase in proportion to the desired stretch ratio.

[0107] The biaxially stretched film then passes through a third zone 26 where it is heated and heat-treated or relaxed, as described for the transverse stretching device. In this case, the lateral distance between the opposing grippers can be reduced, and the speed of the opposing grippers can also be reduced compared to the stretching zone.

[0108] In the exit area, the film is released from the gripping devices (clips) by suitable means and released from the co-stretching device.

[0109] (5) Heat treatment process

[0110] After stretching, the thin film is preferably subjected to a heat treatment (stabilization or annealing), in which the thin film is held at an elevated temperature for a specific period of time. The heat treatment is preferably carried out in the third zone 26 immediately after stretching in the transverse or co-stretching device.

[0111] During the heat treatment of the third region 26, the internal stresses in the film caused by stretching are relaxed or eliminated, thereby harmonizing and matching physical properties throughout the film.

[0112] (6) Relaxation

[0113] It is preferred to relax the film during heat treatment to remove or relieve internal stresses in the film and achieve the desired reduction in stretch ratio.

[0114] For example, in sequential stretching, the distance between the opposing transport rails in the third region 26 is narrowed to relax the film only in the lateral direction.

[0115] In the simultaneous stretching process, the film is relaxed in both the machine and transverse directions, for example, by decreasing the transverse distance between the opposing grippers and slowing the speed of the grippers relative to the conveying speed in the stretching zone to achieve the desired degree of relaxation.

[0116] In the thin film production method of the present invention, the relaxation degree is more advantageously in the range of 2% to 15%, preferably 7% to 12%. In simultaneous stretching, it is preferable to apply the relaxation degree in both directions. Relaxation reduces the shrinkage of the thin film.

[0117] (7) Winding process

[0118] The biaxially stretched (stretched) thin film is wound up on a winder.

[0119] The side edges of the thin film, which is gripped by a plurality of gripping devices, are previously cut longitudinally, and the thin film is then wound onto a winder.

[0120] If desired or required, the film may be surface treated before final rolling.

[0121] Finally, the film is wound up on a winder.

[0122] (8) Additional processing

[0123] The biaxially oriented thin films produced according to the present invention can be further processed in additional processing steps.

[0124] For example, the film may be cut and rolled before further processing.

[0125] Other possible processing steps are, inter alia, metallization, thinning, coating (anti-permeation coating, protective coating), printing, surface treatment, laser processing, lacquering, etc. It is preferred to metallize the thin film.

[0126] A further embodiment of the present invention is the use of thin films, especially metallized thin films, as dielectrics for the manufacture of the batteries described herein. [Brief explanation of the drawings]

[0127] [Figure 1] Schematic plan view of a transverse stretching device [Figure 2] Left photomicrograph showing the front side of the thin film of the present invention that contacts the chill roll surface during production, and right photomicrograph showing the back side of the thin film. [Figure 3] Graph showing the maximum possible longitudinal stretch ratio (MDx) of 3.8 μm-thick films containing only cycloolefin polymers with different contents, stretched sequentially and simultaneously.

[0128] List of Abbreviations BO biaxially oriented; BOPP biaxially oriented polypropylene; COC cycloolefin polymer, especially cycloolefin copolymer; MD machine direction; PP polypropylene; TD transverse direction; Tg glass transition temperature DETAILED DESCRIPTION OF THE INVENTION [Example]

[0129] Measurement method: Film thickness: DIN 53370 Layer thickness: DFN-ISO 3146 Crystalline melting point, glass transition temperature and crystallinity: International Organization for Standardization standard 11357-1, -2, -3 (DSC, heating rate 10K / min) Melt Resin Flow Index: International Organization for Standardization Standard 1133 Heat shrink ratio: DIN-ISO standard 11501 Surface roughness: German European Industrial Standard - International Organization for Standardization Standard 4287 Breakdown voltage: German European Industrial Standard 60243-2 Loss factor and dielectric constant: German European Industrial Standard 60674-2 (VDE)

[0130] material Polypropylene: Borclean® HC300BF (crystal melting point 164°C) Melt resin fluidity index (230℃ / 2.16kg): 3.3g / 10min Metallizable polypropylene for thin dielectric films in batteries Ultra-high purity, ash content less than 20ppm, Metal Content: Titanium < 3ppm, Aluminum < 3ppm, Chloride < 3ppm Cycloolefin polymer 1 (COC1): Topas COC 6013 M07 Copolymer of norbornene and ethylene Glass transition temperature: 142°C Molten resin fluidity index (260℃, 2.16 kg) 13.26 g / 10 min Cycloolefin polymer 2 (COC2): Topas COC 6015 S04 Copolymer of norbornene and ethylene Glass transition temperature 158°C Molten resin fluidity index (260℃, 2.16 kg) 4.08 g / 10 min

[0131] The thin film manufacturing method of the present invention. Granular polypropylene, cycloolefin polymer 1, and cycloolefin polymer 2 were melted (in one batch) in a twin-screw extruder maintained at a temperature of 250°C to 260°C and placed on a chill roll using an open die. A thin film was pressed onto the chill roll using a conventional high-pressure air knife. The surface temperature of the chill roll was maintained in the range of 90°C to 95°C. No cooling bath was used.

[0132] Multiple thin films were fed into a simultaneous stretching apparatus (only for Examples 1, 3, 4, and 5). The simultaneous stretching apparatus was divided into multiple heating zones, and in each heating zone, the thin films were heated to the temperatures shown in Table 1. Each thin film was heated evenly from above and below. The first zone 22, the second zone 24, and the third zone 26 were divided into multiple different heating zones as shown in the table below.

[0133] Temperature range during stretching (simultaneous biaxial stretching method) [Table 1]

[0134] The films of Examples 1, 4, and 5 were simultaneously stretched with a longitudinal modulus of 6.1 and a transverse modulus of 9.9. The relaxation (relaxation) amounts in the longitudinal and transverse directions were 10%. The effective longitudinal stretch ratio was 5.5, the effective transverse stretch ratio was 9, and the areal stretch ratio was 50. The longitudinal stretch ratio used in Example 3 was 5.

[0135] In Example 2, sequential stretching was applied. First, a thin film was fed into a longitudinal stretching apparatus (MDO). The thin film was introduced into the longitudinal stretching apparatus by multiple heated rollers with different speeds, and the thin film was stretched in the longitudinal direction. The rollers had the temperatures shown in Table 2.

[0136] Longitudinal stretching device [Table 2]

[0137] The thin film stretched in the machine direction was then fed to a transverse stretching apparatus (TDO) and stretched in the transverse direction. The thin film was reheated in the preheating zone (first zone 22), stretched in the stretching zone (second zone 24), and heat-treated (annealed) in the third zone 26 to relax (shrink) 10% in the transverse direction. The thin film was heated at the zone temperatures shown in Table 3. The top and bottom of multiple thin films were heated evenly.

[0138] Lateral stretching device [Table 3]

[0139] The thin film must be produced stably and reliably to avoid cracking of the thin film. For this purpose, it was necessary to reduce the longitudinal stretching ratio and the surface stretching ratio in Examples 2 and 3. The longitudinal stretching ratio used in Example 2 was 3.7.

[0140] Two thin films of the present invention were prepared and comparative tests were carried out three times. The thin film data are shown in Table 4 below.

[0141] Composition and Properties [Table 4] *Comparative experiment **Weighted arithmetic mean value of the glass transition temperatures Tg of cyclopolyolefin polymers 1 and 2 ***sim = simultaneous, seq = sequential

[0142] In Examples 1 and 3, in accordance with Patent Document 10, only one type of cycloolefin polymer was used, and the polymer content of the polymer mixture was increased to improve temperature resistance. As a result, it was found that when the cycloolefin polymer content was increased by 5 wt. % during simultaneous stretching, the areal stretch ratio had to be reduced to ensure stable production (ensuring sufficient running stability). Only in this way could a strip-shaped thin film material be produced while avoiding cracking of the thin film. In particular, the elongation in the machine direction had to be reduced. As shown in Patent Document 10, increasing the thin film thickness instead of reducing the stretch ratio can prevent cracking of the thin film during production. However, in the case of thin films for storage batteries, a large film thickness results in a disadvantage of increased volume for the same capacity of the storage battery. For example, in many applications, such as automotive engineering, installation space is extremely limited, resulting in a disadvantage of increased volume. In Examples 4 and 5 of the present invention, a decrease in the areal stretch ratio is not necessary if the thin film thickness is the same. Furthermore, in Example 5, the breakdown voltage improved by approximately 10%.

[0143] The shrinkage values ​​in the transverse direction at 140°C for the examples of the present invention shown in Table 4 also show some improvement over the examples outside the scope of the present invention.

[0144] Conventional metallization (surface plating for DC circuit applications) was applied to the thin film for storage batteries, and batteries were fabricated from each metallized thin film to investigate the effect of the present invention on the electrical properties of the thin film. The storage batteries were exposed to various test voltages for 3000 hours in a warming cabinet at temperatures between 125°C and 135°C. As a result, various electric field strengths were obtained, as shown in Table 5. The electric field strength is the quotient of the voltage [V] and the thin film thickness [μm] (3.8 μm in this embodiment). Storage batteries that exhibited an electrical short circuit were counted as failed. The capacity deviation (dC / C) and the change in the battery loss factor were investigated at specified times (1000 hours, 2000 hours, and 3000 hours). In addition, storage batteries in which the obtained data significantly deviated from the initial values ​​were also counted as failed. The test results are shown in Table 5. Examples 1 to 3 are comparative tests.

[0145] Electrical characteristics [Table 5] *Field strength OK = After 3000 hours, all batteries were still within limits. Failure = Short circuit failure or failure due to high capacitance deviation or high loss factor. -=No measurement.

[0146] As is clear from Table 5, the high-temperature electrical properties of the thin films of the present invention are clearly superior. In tests at a temperature of 125°C and electric field strengths of 200 V / μm and 250 V / μm, the thin films of the present invention in Examples 4 and 5 completely passed the test without any failures. The thin films of Comparative Experiments 1 to 3 all failed at 250 V / μm, and only the thin film of Comparative Experiment 1 passed the test at 200 V / μm. The thin film of Comparative Experiment 3 showed no measurable condition at 200 V / μm and became unusable due to short circuits at 125°C and 250 V / μm.

[0147] The thin film in the comparative test at 135°C failed all tests conducted. The thin film of Example 5 passed all electric field strength tests, and the thin film of Example 4 passed even an electric field strength of 140 V / μm. These thin films only failed due to excessive capacity shift at 200 V / μm. Therefore, the thin film of the present invention clearly has excellent electrical properties at high temperatures, and unlike conventional storage batteries, the thin film of the present invention can be used in high-temperature applications in the automotive industry.

Claims

1. a) at least two cycloolefin polymers; b) at least one semicrystalline α-olefin polymer; In a biaxially oriented thin film comprising the total content range of all cycloolefin polymers in the thin film is 10% by weight to 25% by weight, all cycloolefin polymers contained in the thin film have a glass transition temperature in the range of 120° C. to 180° C., the thin film comprises at least a first cycloolefin polymer and a second cycloolefin polymer, the second cycloolefin polymer having a higher glass transition temperature than the first cycloolefin polymer; The total content range of all semi-crystalline α-olefin polymers contained in the thin film is 75% by weight to 99% by weight, and all semi-crystalline α-olefin polymers contained in the thin film have a crystalline melting point in the temperature range of 150° C. to 170° C.; and A biaxially oriented thin film characterized in that the weighted arithmetic average of the glass transition temperatures of all cycloolefin polymers contained in the thin film is equal to or lower than the weighted arithmetic average of the crystalline melting points of all semi-crystalline α-olefin polymers contained in the thin film, and the total amount is expressed as a value relative to the total mass of the thin film.

2. The biaxially oriented thin film according to claim 1, wherein the thin film contains only one type of semicrystalline α-olefin polymer, and the weighted arithmetic average of the glass transition temperatures of all cycloolefin polymers contained in the thin film is equal to or lower than the crystalline melting point of the semicrystalline α-olefin polymer.

3. 3. The biaxially oriented thin film of claim 1 or 2, wherein the thin film comprises only one semicrystalline α-olefin polymer, which is polypropylene.

4. 2. The biaxially oriented thin film according to claim 1, wherein the entire cycloolefin polymer is a copolymer containing norbornene and ethylene as monomers.

5. 2. The biaxially oriented thin film according to claim 1, wherein the total content of all semicrystalline α-olefin polymers contained in the thin film is in the range of 75% by weight to 90% by weight.

6. 2. The biaxially oriented thin film of claim 1, wherein the glass transition temperature of the second cycloolefin polymer is at least 3[deg.] C. higher than the glass transition temperature of the first cycloolefin polymer.

7. The biaxially oriented thin film according to claim 1, wherein the thin film contains only one semicrystalline α-olefin polymer which is polypropylene, the thin film does not contain any other cycloolefin polymer other than the first cycloolefin polymer and the second cycloolefin polymer, and both the first cycloolefin polymer and the second cycloolefin polymer contain norbornene and ethylene as monomers.

8. 2. The biaxially oriented thin film according to claim 1, wherein the thin film contains the first cycloolefin polymer and the second cycloolefin polymer in a content range of 5% by weight to 15% by weight, respectively.

9. A multi-layered thin film comprising at least one layer of the thin film of claim 1.

10. 10. The biaxially oriented thin film of claim 1, wherein the thin film has a maximum longitudinal heat shrinkage of 5% and a maximum transverse heat shrinkage of 0.5% when measured at 130° C. after 5 minutes according to International Organization for Standardization standard 11501.

11. 2. The biaxially oriented thin film of claim 1, wherein the longitudinal and transverse surface roughnesses Ra of the thin film are in the range of 0.02 μm to 0.2 μm as measured according to European Standard, International Organization for Standardization Standard 4287.

12. 2. The biaxially oriented thin film according to claim 1, wherein the thickness of the thin film is in the range of 2 μm to 10 μm.

13. 10. The biaxially oriented thin film of claim 1, wherein the thin film has one or both sides metallized.

14. 2. Use of the biaxially oriented thin film according to claim 1 as a dielectric for producing a storage battery.

15. A storage battery comprising the thin film according to claim 1.

16. a) at least two cycloolefin polymers; b) at least one semicrystalline α-olefin polymer; In a biaxially oriented thin film comprising the total content range of all cycloolefin polymers in the thin film is 10% by weight to 25% by weight, all cycloolefin polymers contained in the thin film have a glass transition temperature in the range of 120° C. to 180° C., the thin film comprises at least a first cycloolefin polymer and a second cycloolefin polymer, the second cycloolefin polymer having a higher glass transition temperature than the first cycloolefin polymer; The total content range of all semi-crystalline α-olefin polymers contained in the thin film is 75% by weight to 99% by weight, and all semi-crystalline α-olefin polymers contained in the thin film have a crystalline melting point in the temperature range of 150° C. to 170° C.; and A method for producing a biaxially oriented thin film, the weighted arithmetic average of the glass transition temperatures of all cycloolefin polymers contained in the thin film being equal to or lower than the weighted arithmetic average of the crystalline melting points of all semi-crystalline α-olefin polymers contained in the thin film, the total amount being expressed as a value relative to the total mass of the thin film, forming, in particular by extrusion, a thin film containing at least two cycloolefin polymers and at least one semicrystalline α-olefin polymer; stretching the extruded film in the machine and transverse directions to form a biaxially oriented film; and rolling the formed biaxially stretched thin film.

17. 17. The method of claim 16, wherein the biaxially stretched film has an areal stretch ratio of at least 40.

18. 17. A process for producing a biaxially oriented thin film according to claim 16, wherein stretching is carried out in the machine direction and the transverse direction simultaneously, or the film is first stretched in the machine direction and the machine direction stretched film is then stretched in the transverse direction.

19. subjecting the biaxially stretched film to a heat treatment; contracting the biaxially stretched film to a predetermined areal stretch ratio through a relaxation process; 17. The method for producing a biaxially oriented thin film according to claim 16, comprising one or both of the steps:

Citation Information

Patent Citations

  • Semi-crystalline cycloolefin copolymer film

    CA2115196C

  • Cycloolefin polymer compositions, molded bodies and their uses

    DE102010034643A1

  • Longitudinal stretching unit for film stretching equipment used during manufacture of film web, has three stretching roll groups among which any two roll groups are positioned in different elevation with respect to third roll group

    DE102011109385A1

  • Film capacitor

    DE102017118202A1

  • A thermally formable thermoplastic polyolefin film useful as a carrier film and having very good thermal formability, good barrier properties against water, and outstanding punching behavior

    DE10242730A1